Application of KOMPAS-3D for the development of a belt conveyor drive - Kolodii, S. (ТДАТУ, 2018)
We are currently involved in computer technology. Computer technology is playing a leading role today. With the development and growing role of computers and computer technologies, there is an increasing need for writing programs for different purposes. In our time, we can not imagine working without a computer, therefore we used KOMPAS-3D for the development of a belt conveyor drive.
Keywords: KOMPAS-3D; Master CAM; AutoCAD; drive